Design and characterization of a mucoadhesive nanoparticle-loaded thermo-responsive in-situ nasal gel for enhanced brain delivery of an antimigraine drug - Mansi Butola; Vikash Jakhmola (Journal of Applied Pharmaceutical Research, 2026)
Background: Migraine is a debilitating neurological disorder that requires rapid and effective drug delivery to the brain. Conventional oral and parenteral therapies are associated with delayed onset of action, low patient compliance, limited central nervous system (CNS) bioavailability due to the blood-brain barrier (BBB), and hepatic first-pass metabolism. This study aimed to develop a thermoresponsive, mucoadhesive, nanoparticle-loaded nasal in situ gel to enhance brain delivery of an antimigraine drug. Methodology: Drug-loaded nanoparticles were prepared via ionic gelation and incorporated into a thermo-sensitive nasal in situ gel via the cold method. Results and Discussion: The optimized nanoparticle formulation (NP13) exhibited a small particle size (154.3 nm), acceptable polydispersity index (0.3485), positive zeta potential (22.79 mV), high entrapment efficiency (89.09%), drug loading (14.33%), and sustained drug release (90.26%). The developed in situ gel showed optimal pH (6.8), suitable gelling temperature (28–34 °C), viscosity (556 cp), entrapment efficiency (85%), drug content (95.82%), in vitro drug release (88.89 ± 0.98%), and ex vivo permeation (85.24 ± 0.67%) over 10 hours. Histopathological studies confirmed minimal nasal mucosal irritation compared to the drug solution and isopropyl alcohol. MTT assay results demonstrated concentration-dependent cytotoxicity, with SS-NPs ISG4 showing higher cell viability than the free drug, indicating reduced cytotoxicity due to nanoparticle encapsulation. Blank nanoparticles exhibited maximum cell survival, confirming carrier biocompatibility. Conclusion: The developed nanoparticle-loaded nasal in situ gel demonstrated promising safety, biocompatibility, and enhanced delivery potential, validating its suitability for intranasal migraine therapy.